Use of propidium iodide like a celular contrast staining in the direct fluorescent antibody (DFA) test for the rabies viruses diagnostic - Iguala-Vidales, M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Texto em inglês